Eficacy of Paenibacillus sp. Using seed treatment for controlling Bacterial Leaf Blight Caused by Xanthomonas sp. in Rice Plants - Al Rahmad, Nirmala Putri; Purnawati, Arika; Prasetyawati, Endang Triwahyu (CROPSAVER, 2025)
Rice (Oryza sativa L.) is one of the important food commodities consumed by the Indonesian people. One of the reasons for the decline in rice production is infection by the pathogen Xanthomonas oryzae pv. oryzae (Xoo) which causes bacterial leaf blight (BLB) and it’s seed-borne pathogen. The purpose of the experiment is to to evaluate the effectiveness of seed soaking using Paenibacillus sp. to control BLB in rice plants. Efforts to control BLB and improve rice plant growth were carried out by seed treatment using biocontrol agent has potential as biological control for BLB in rice plants by producing antibiotic. This experiment used a Completely Randomized Design with 4 treatments (control, Paenibacillus sp., Bacillus sp. BTH22, Paenibacillus polymyxa) and 5 replications. Data analysis was performed using analysis of variance (ANOVA) at a 5% significance level using IBM SPSS Statistics version 22 software. If the analysis results showed significant differences between treatments, an Honestly Significant Difference (HSD) test was performed at the 5% level. The research results showed that seed soaking using Paenibacillus sp. was able to reduce the incubation period of HDB disease by up to 11 days, with the lowest disease attack intensity being 10.21%, the highest seed germination rate being 91.25%, and an efficacy level of 53.32%.